Pengaruh geopolitik terhadap stabilitas ekonomi dan politik indonesia - Zahra, Cintia Nabila (Maliki Interdisciplinary Journal, 2026)
Geopolitics is the study of the relationship between geographical conditions and a country's political, economic, and security strength. This study aims to analyze the influence of geopolitics on Indonesia's economic and political stability and to examine Indonesia's strategic role as the Global Maritime Axis in international relations. The research method used is descriptive qualitative, with a literature review approach through data collection from various journals, books, and related scientific sources. The results show that Indonesia's strategic geographic position provides significant opportunities for international trade, maritime sector development, and strengthening global diplomacy. However, global geopolitical dynamics also pose various challenges, such as investment threats, economic and monetary volatility, and dependence on the global economy. Therefore, Indonesia needs to strengthen national resilience through international cooperation, strengthening the economic and maritime sectors, sustainable infrastructure development, and improving diplomacy and the quality of human resources to effectively face global geopolitical challenges.